Alkylative/arylative carboxylation of unsaturated hydrocarbons utilizing CO2 as C1 synthon: An update. Issue 52 (October 2021) - Cao, Yan; A. Dhahad, Hayder; Hussen, Hasanen M.; E. Anqi, Ali; Farouk, Naeim; Issakhov, Alibek; Heravi, Mohammad Reza Poor
Graphical abstract: This review article provides a concise and update overview of the current status and latest methodologies on the synthesis of structurally complex carboxylic acids and derivatives through the direct carbocarboxylation of unsaturated hydrocarbons using CO2 as a carboxyl source developed in the last two decades. Highlights: Comprehensive overview of the carbocarboxylation of unsaturated hydrocarbons utilizing CO2 as the carbonyl source. Carbocarboxylation of alkyne feedstocks with CO2 to give acrylic acid derivatives. The synthesis of saturated carboxylic acids from alkenes. Carbocarboxylation of 1, 3-dienes with organozinc reagents and CO2 using a nickel(0). Carbocarboxylative cyclization of terminal allenes with aryl aldehydes and CO2 . Abstract: The difunctionalization of unsaturated hydrocarbons, the incorporation of two functional groups onto an unsaturated carbon-carbon bonds, is one of the most active and popular topics in modern organic chemistry due to its significance in the rapid and highly atom economical synthesis of complex molecules from simple starting materials within a single click. Among various difunctionalization reactions, difunctionalizing carboxylations utilizing CO2 as a renewable and environmental friendly C1 feedstock has attracted more and more attention in recent years. In this regard, several interesting strategies have been developed in the last two decades for the preparation of branched carboxylic acids and their derivatives through the alkylative/arylative carboxylation of the corresponding unsaturated hydrocarbons using CO2 as a carboxyl source. Thus, it is an appropriate time to summarize those advances. The purpose of this Mini-Review is to focus on the most important advances and developments on the attractive research field with particular emphasis on the mechanistic features of the reaction pathways. Notably, we have organized this review based on the type of bond where the CO2 insertion occurs.